Determinants of Capital Structure:Evidence from UK Panel Data - Reimoo, Zehra (2007)
The study investigates the determinants of capital structure of 173 non financial UK listed companies from 1998-2007 using three panel estimation models. This study also compares the results of pooled OLS results with the fixed effects estimation models, which has limited evidences in the literature. The results of the study reveals that when using fixed effects there are slight changes in the significance level of the variables and more importantly in the sign of the relationships which is consistent with the studies of Bevan and Danbolt (2004) and Berger, Ofek and Yermack. (1997). Overall, the result of the study suggests that large companies rely on long term debt levels, growth opportunities are inversely related to the level of borrowing, profitable firms in United Kingdom relies on internal finance, liquid firms are inclined to raise long term debt, firms that have unique products stay away from debt as they face higher costs of liquidation and bankruptcy and the availability of collateral for firms is an important aspect to raise debt but doesnÃÂÃÂ¢ÃÂÃÂÃÂÃÂt holds true when firms are in need of short term finance. Lastly, it was found that the availability of non-debt tax shields have insignificant influence on capital structure.